Analysis of molekular interactions in ribosomal RNA and ribozymes - Mládek, Arnošt (2008)
Trans Hoogsteen/Sugar Edge (Ho/SE) pairing patterns are of key importance at stabilizing loop geometries in RNA. The goal of this thesis is to provide a detailed quantum chemical characterization of this base pair family both in gas-phase and aqueous solution. DFT-optimized geometries and RI-MP2 interaction energies is reported for the 10 crystallographically identified members of the family. Balance of intermolecular stabilizing forces in the trans Ho/SE base pairs are very similar to that of trans Watson-Crick/Sugar edge (WC/SE) base pairs. Thus, albeit the electron correlation component remarkably contributes to the stabilization, its relative importance is noticeably lower than in the cis WC/SE or cis and trans SE/SE edge base pairs. In two pairs, i.e. C/rC and G/rG, the electrostatic component is clearly superior to the correlation contribution, due to the fortunate orientation of the molecular dipoles of the component bases. In contrast, in the A/rG pair, which is the most stable.